Marketing fashion footwear the business of shoes - Armstrong-Gibbs, Fiona; McLaren, Tamsin (Bloomsbury, 2017)
"Marketing Fashion Footwear addresses the strategic issues surrounding the marketing and distribution of footwear, including brand identity, consumer behavior, production and manufacturing, and the impact of globalization and regional trends"--Provided by publisher.